Compiling Haskell by Program Transformation: A Report from the Trenches - Peyton Jones, Simon (Proceedings European Symposium on Programming (ESOP'96), 1996)
Many compilers do some of their work by means of correctness-preserving, and hopefully performance-improving, program transformations. The Glasgow Haskell Compiler (GHC) takes this idea of "compilation by transformation" as its war-cry, trying to express as much as possible of the compilation process in the form of program transformations. This paper reports on our practical experience of the transformational approach to compilation, in the context of a substantial compiler.See "A transformation-based optimiser for Haskell" (SCP 1997) for a journal version of this paper.